Cosmic‐ray exposure ages of pallasites. (January 2015) - Herzog, G. F.; Cook, D. L.; Cosarinsky, M.; Huber, L.; Leya, I.; Park, J.
Abstract We analyzed cosmogenic nuclides in metal and/or silicate (primarily olivine) separated from the main‐group pallasites Admire, Ahumada, Albin, Brahin, Brenham, Esquel, Finmarken, Glorieta Mountain, Huckitta, Imilac, Krasnojarsk, Marjalahti, Molong, Seymchan, South Bend, Springwater, and Thiel Mountains and from Eagle Station. The metal separates contained an olivine fraction which although small, <1 wt% in most cases, nonetheless contributes significantly to the budgets of some nuclides (e.g., up to 35% for 21Ne and 26Al). A correction for olivine is therefore essential and was made using model calculations and/or empirical relations for the production rates of cosmogenic nuclides in iron meteoroids and/or measured elemental concentrations. Cosmic‐ray exposure (CRE) ages for the metal phases of the main‐group pallasites range from 7 to 180 Ma, but many of the ages cluster around a central peak near 100 Ma. These CRE ages suggest that the parent body of the main‐group pallasites underwent a major break‐up that produced most of the meteorites analyzed. The CRE age distribution for the pallasites overlaps only a small fraction of the distribution for the IIIAB iron meteorites. Most pallasites and IIIAB irons originated in different collisions, probably on different parent bodies; a few IIIABs and pallasites may have come out of the same collision but a firm conclusion requires further study. CRE ages calculated from noble gas and radionuclide data of the metal fraction are higher on average than the 21Ne exposure ages obtained for the olivine samples. As the metal and olivine fractions were taken in most cases from different specimens, the depth‐dependency of the production rate ratio 10Be/21Ne in metal, not accounted for in our calculations, may explain the difference.